Synthesis and characterization of nano-micronutrient fertilizer and its effect on nutrient availability and maize (Zea Mays L.) productivity in calcareous soils - Dalal H. Sary; Mahmoud E. Abd El-Aziz (Scientific Reports)
Abstract Agriculture in calcareous soil faces challenges such as high calcium carbonate content, low organic matter, and poor availability of nutrients. Therefore, a field experiment was done during the summer seasons of 2022 and 2023 at the Nubaria Research Station in Egypt to study the effect of nano-fertilizers (NFs) on maize productivity and nutrient availability. The field experiment was done through a randomized completely block design with treatments: Control, Nano-Zn 20 mg/L, Nano-Zn 40 mg/L, Zn-chelate 2 g/L, Nano-Mn 20 mg/L, Nano-Mn 40 mg/L, Mn-chelate 2 g/L, Nano-Mo 20 mg/L, Nano-Mo 40 mg/L and ammonium molybdate (AMo) 250 mg/L. The synthesized nano-micronutrient fertilizers were analyzed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The results showed that 40 mg/L of NFs was the most effective treatment for most studied traits. The highest maize grain weight per plant (239.4 g), 100-grain weight (40.7 g), and yield (15.1 ton/ha) were obtained with 40 mg/L of Nano-Mo, Zn, and Mn, respectively. The maximum leaves nutrient contents of P (0.98%), K (1.0%), Fe (268 mg/kg), Zn (79 mg/kg), and Cu (24.3 mg/kg) were found in plants treated with Nano-Zn 40 mg/L. While, the highest concentrations of Mn (271.7 mg/kg) and N (3.96%) on the leaves were obtained with 40 mg/L of Nano-Mn and Mo, respectively. When compared to traditional fertilizers, NFs showed better plant growth traits, productivity, and nutrient levels.